Developmental Venous Anomaly Responsible for Hemifacial Spasm. Issue 2 (1st April 2013) - Chiaramonte, R.; Bonfiglio, M.; D'Amore, A.; Chiaramonte, I.
Hemifacial spasm (HFS) is a facial movement disorder characterized by involuntary, unilateral and intermittent contractions of the facial muscles. It is one of the syndromes related to neurovascular conflict, first described by Jannetta et al. in 1979. Typically, HFS is due to pulsatile compression by the anterior inferior cerebellar artery. We describe a rare case of left developmental venous anomaly in a 59-year-old man referred to us with a six-month history of left-sided HFS. We performed an MR study of the brain and cerebellopontine angles, which demonstrated a compression of the ipsilateral facial nerve by the developmental venous anomaly.